Padrões fenológicos vegetativos e reprodutivos de Hymenaea martiana Hayne em resposta as variáveis ambientais e avaliação das alterações fisiológicas de suas sementes armazenadas - Pádua, Guilherme Vinicius Gonçalves de (2024)
Phenological studies are essential for understanding ecosystems and guiding conservation and agricultural management practices, influencing the timing of activities such as planting, harvesting, and pest control. These studies are also fundamental for assessing and adapting agriculture to climate change. The species Hymenaea martiana, found in the Northeast of Brazil, stands out due to its botanical characteristics and favorable properties for the construction industry, given its dense wood. Furthermore, it is valued in traditional Brazilian medicine, being used to treat inflammatory conditions, infections, rheumatism, and anemia, due to the medicinal compounds present in the plant. In this context, the objective was to evaluate the influence of environmental variables on the vegetative and reproductive phenological patterns of H. martiana, as well as the physiological changes in its seeds under different storage conditions. Two experiments were conducted, which are described as follows: I - Phenology: This experiment was conducted through field observations in five areas of H. martiana in Areia-PB, from May 2021 to April 2023. Every 30 days, phenological events such as budding, senescence, floral bud formation, flowering, and fruiting were evaluated. Circular statistical analyses were employed to examine the occurrence, concentration, seasonality, and duration of these phenological periods. Additionally, Spearman correlations were used to test the relationship between meteorological variables and the observed phenophases during the study period. II - Storage: This experiment was conducted at the Seed Analysis Laboratory (LAS) at the Federal University of Paraíba, from January 2021 to January 2023. H. martiana seeds were stored in different types of packaging (semi-permeable polyethylene, kraft paper, and cloth) under laboratory conditions (T = 27 ± 4 °C; RH = 60%). Evaluations occurred every three months over a 24-month period, using a completely randomized experimental design in split plots. The packaging types were considered the main plots (with 3 levels), and the storage periods were the subplots (with 9 levels). Physical analyses (water content) and physiological analyses (emergence test, first count, emergence percentage, emergence speed index, seedling length, and dry mass) were performed during each evaluation. Data analysis involved variance analysis and polynomial regression concerning the storage periods. H. martiana exhibits an annual seasonal pattern of phenophases, including budding, senescence, floral bud formation, and flowering. The average dates vary among the areas, with budding occurring in August (area 2), October (areas 1, 4, and 5), and November (area 3). Senescence occurs in July (area 2) and August (areas 1, 3, 4, and 5). Flowering happens in January (areas 3 and 4), March (area 2), and December (areas 1 and 5). Precipitation significantly influenced these events. The harvesting of H. martiana fruits is recommended in October, November, and December under highland conditions. The storage of H. martiana seeds in cloth, paper, and semi permeable polyethylene containers for 24 months induces alterations and limitations in seedling vigor.